Investigating the central nervous system disposition of actinomycin D: implementation and evaluation of cerebral microdialysis and brain tissue measurements supported by UPLC-MS/MS quantification - Benzel, Julia; Bajraktari-Sylejmani, Gzona; Uhl, Philipp; Davis, Abigail; Nair, Sreenath; Pfister, Stefan; Haefeli, Walter E.; Weiß, Johanna; Burhenne, Jürgen; Pajtler, Kristian Wilfried; Sauter, Max (Pharmaceutics, 2021)
Actinomycin D is a potent cytotoxic drug against pediatric (and other) tumors that is thought to barely cross the blood-brain barrier. To evaluate its potential applicability for the treatment of patients with central nervous system (CNS) tumors, we established a cerebral microdialysis model in freely moving mice and investigated its CNS disposition by quantifying actinomycin D in cerebral microdialysate, brain tissue homogenate, and plasma. For this purpose, we developed and validated an ultraperformance liquid chromatography-tandem mass spectrometry assay suitable for ultra-sensitive quantification of actinomycin D in the pertinent biological matrices in micro-samples of only 20 µL, with a lower limit of quantification of 0.05 ng/mL. In parallel, we confirmed actinomycin D as a substrate of P-glycoprotein (P-gp) in in vitro experiments. Two hours after intravenous administration of 0.5 mg/kg, actinomycin D reached total brain tissue concentrations of 4.1 ± 0.7 ng/g corresponding to a brain-to-plasma ratio of 0.18 ± 0.03, while it was not detectable in intracerebral microdialysate. This tissue concentration exceeds the concentrations of actinomycin D that have been shown to be effective in in vitro experiments. Elimination of the drug from brain tissue was substantially slower than from plasma, as shown in a brain-to-plasma ratio of approximately 0.53 after 22 h. Because actinomycin D reached potentially effective concentrations in brain tissue in our experiments, the drug should be further investigated as a therapeutic agent in potentially susceptible CNS malignancies, such as ependymoma.